Pelatihan Literasi Sains Untuk Meningkatkan Keterampilan Berpikir Ilmiah Guru Sekolah Dasar di Slempit Kabupaten Gresik - Subayani, Nataria; Bakhtiar, Afakhrul Masub (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2023)
Science learning in elementary schools requires real examples in everyday life in order to facilitate the construction of students' thinking at the level of concrete operational cognitive development. This requires a skill needed by teachers in designing science learning to be contextual. Examples of concepts that are far away and difficult to find by students in the surrounding environment, causing students to lack interest in learning science. Meanwhile, teachers feel less confident in presenting examples of science concepts that are appropriate to their respective regions because they are not contained in the guidebooks used in learning in class. This service aims to provide scientific literacy (IPA) training to teachers at UPT SDN 209 Gresik so that the science learning process is in accordance with the surrounding environment and has a positive effect on scientific literacy and scientific thinking skills of teachers. The service program is carried out through workshops for teachers. The results of this service are in the form of examples of science concepts related to the daily life of the Slempit community related to the context of science (IPA) and drafts of scientific articles for elementary school teachers